Time-varying reliability modelling and quasi-static accuracy optimization of precision CNC machine tools. (October 2020) - Guo, Shijie; Pang, Bo; Jiang, Gangjun; Chen, Hongxia; Li, Zhiqiang
Abstract: Aiming at the influence of time-varying characteristics of geometric error on precision CNC machine tool quasi accuracy retention, a time-varying reliability accuracy maintenance method based on multi-objective reliability and maintenance cost tradeoff is proposed. Firstly, on the basis of geometric error transfer model and Achard adhesive wear theory, a quasi-static accuracy reliability limit state function to meet time-varying characteristics is established and the time-varying accuracy reliability is solved based on the First order second moment method. Secondly, according to the time-varying characteristics of the quasi-static accuracy of machine tools, the maintenance cost model and reliability multi-objective optimization model are established, and the trade-off between cost and reliability function is realized. Finally, the optimization results of three-axis machining center show that the method can realize the optimization of geometric accuracy and determine the quasi-static error compensation value which meets the requirements of reliability accuracy.